A Documentary Film Sahasra Warsa: Reviving A Thousand Years of Painting in Batuan Village, Gianyar : - Martida, Vanesa; Setem, I Wayan; Wirakesuma, I Nengah (Journal of Art, Film, Television, Animation, Games and Technology, 2024)
This documentary film defines 'sahasra warsa' (a thousand years) of painting in Batuan Village, Sukawati Sub-District, Gianyar, Bali Province, Indonesia. The existence of painting in Batuan Village is proven to have a long history, referring to the Baturan inscription 944 caka (1022 AD) of the reign of King Marakata. The king created the term 'citrakara' as recognition of community with the painting profession. In the 1930s, the presence of Pita Maha and the visit of anthropologists Margaret Mead and Gregory Bateson also contributed to the development of painting in Batuan Village. Batuan style paintings have been collected by various museums in Indonesia and abroad, including a collection of President Soekarno. The number of Batuan style painters is decreasing year by year. This observational-poetic documentary style includes historical information, the characteristics of Batuan painting, as well as efforts to preserve it. This documentary aims at serving as an audio-visual archive as well as a learning medium for future generations.